MODIFICATION OF THE NUSS PROCEDURE-PREVENTION OF INJURIES OF THE HEART AND MAJOR BLOOD VESSELS - Å½ganjer, Mirko (BALI MEDICAL JOURNAL, 2012)
Objective: The Nuss procedure is a widely accepted technique for correcting pectus excavatum. Unfortunately, fatal complications such as cardiac perforation and injury of the great blood vessels have been noticed in a few patients.We modified original Nuss technique to be simpler and less dangerous. Methods: We modified Nuss procedure with the sternal elevation to improve sternal depression. Modified Nuss procedure was carried out by applying metal lifter raise sterum until the patient starts to raise from the operating table. The space behind sternum is now wider, and surgery has become safer with less probability of injuries intrathoracic organs. We compared 46 patients operated by the original Nuss method (taking into account the data from the literature on complications of the original method on a large series of patients) with 54 patients operated by a modified Nuss method. Results: Before lifting the sternum depth of the deformity was between 2.9 and 6.2 cm (mean 5.4 cm), and the increase were between 1.5 and 4.0 cm (mean 2.8 cm). The difference of 2.6 cm is large enough, and the width of introducer and bars are about 3 mm for  securely passed along the chest. Conclusions: A modified method of treating pectus excavatum is safer, better and with fewer complications than the original method of Nuss.